Effects of deep breathing training on exercise-induced changes of cardiovascular parameters in normal young volunteers - Ramaloo, R Gobhy AL (2004)
Deep breathing exercise is found to be useful technique in bringing out changes in physiological and pathological conditions in cardiovascular system. Keeping this in view, the present study was designed to see the effect of deep breathing training on exercise-induced changes of cardiovascular parameters in normal young volunteers. Effects of Deep breathing training on exercise-induced changes of cardiovascular parameters were studied in nonnat young healthy student volunteers. Thirty-four college students were divided randomly into two groups of 17 each. Experimental group practiced Deep Breathing Exercise daily 15 minutes in the morning and evening. The control group did not do breathing training. Breathing exercise was done for three weeks. Basal recording was done on the first day and at the end of first week, second week and third week. The recording was repeated after deep breathing training. Recording was done before and after physical exercise. The parameters recorded were SBP, DBP and HR. PP, MAP and RPP were calculated from these values. It was noticed that after deep breathing exercise there was a gradual decrease in SBP, PP, MAP, and RPP. But there were no noticeable changes in DBP and HR. This is because the deep breathing exercise enhances the parasympathetic activity and slows down the sympathetic activity.